Trustworthiness and its Relationship to Academic Risky Behaviors among University Students - Ali, Noor Jabbar (Journal of Tikrit University for Humanities, 2024)
Summary of the research: The current research aims to identify: - Trustworthiness among university students - Academic risky behaviors among university students - The correlation between trustworthiness and academic risk-taking behaviors among university students A total of 200 male and female students from the University of Diyala were included in the study sample for the academic year 2022-2023. In order to accomplish the study goals, the researcher constructed a trustworthiness scale based on Rotter’s theory (1980). Regarding the assessment of academic risk-taking behavior, the researcher constructed it based on the theoretical framework proposed by Clifford (1984). The measure has a total of 33 questions, which are split throughout four distinct domains. Specifically, the intellectual domain includes 10 items. There are 9 entries related to behavioral group, 5 items related to social group, and 9 items related to economic and professional group. The psychometric features of the two measures were assessed by the researcher in terms of their validity and reliability. Subsequently, the data was analyzed.